Introduction to Product/Service-System Design - Sakao, Tomohiko; Lindahl, Mattias (Springer London : Imprint: Springer, 2009)
The growing need for companies to address service design, as well as product design, in an integrated manner is becoming increasingly important across a number of industries. Product/Service System (PSS) is a promising business model that companies can use to increase their sustainability in a mature economy. Introduction to Product/Service-System Design contains a collection of practical examples demonstrating how to design a PSS in industry. These recent examples are the results of applying various theories developed in different countries and therefore accommodating diverse cultural differences from throughout Europe and Japan. Providing a useful overall guide to the state of the art in theory and practice, each chapter covers the cutting edge of a different methodology or practice. As any PSS design should, in principle, address the offering, the customer or user, and the provider, the book is arranged according to these three dimensions, providing detailed information on how to incorporate such themes into a working design. The book's focus on design is also evident in the discussion of how to anticipate and utilise the various dynamics within each dimension. Introduction to Product/Service-System Design will help improve working processes and inspire creative thinking for the wide range of people involved in designing a PSS: designers, marketing professionals, sales staff, production engineers, and service engineers. It can also serve as a reference book for university students on advanced courses related to mechanical design, industrial marketing or economics, and production engineering.